2021
DOI: 10.4102/td.v17i1.1008
|View full text |Cite
|
Sign up to set email alerts
|

The power of narrative health communication: Exploring possible effects of first-hand experiential stories on cancer awareness amongst university students

Abstract: Narrative health communication has the potential for effective health promotion about cancer amongst youth from low- and middle-income countries such as South Africa. Sub-Saharan Africa experiences a rising cancer-related disease burden with predicted increase of over 85% by 2030. Whilst promotion through communication, of cancer prevention strategies targeting 18–29 year olds remains scanty, it is crucial for cancer prevention behaviour before the disease develops. The study aimed at examining how narrative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Narratives have been a valuable tool for health promotion in public health through motivating behavior change [33][34][35][36][37][38][39]. This approach has frequently been used for smoking cessation programs [33,34,36], sexual health promotion [40,41], and cancer prevention and control [42,43]. The PICHA7 program used firsthand experiential stories told during participant interviews to explain transmission routes and preventative measures for cholera and severe diarrheal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Narratives have been a valuable tool for health promotion in public health through motivating behavior change [33][34][35][36][37][38][39]. This approach has frequently been used for smoking cessation programs [33,34,36], sexual health promotion [40,41], and cancer prevention and control [42,43]. The PICHA7 program used firsthand experiential stories told during participant interviews to explain transmission routes and preventative measures for cholera and severe diarrheal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found narratives to be a valuable tool for health promotion in the public health field by motivating and supporting behavior change [ 31 , 32 , 33 , 34 , 35 , 36 ]. Narratives have frequently been used for smoking cessation programs [ 30 , 31 , 33 ], sexual health promotion [ 37 , 38 ], and cancer prevention and control [ 39 , 40 ]. Future studies could compare whether the inclusion of narratives facilitates WASH behavior change in cholera hotspots by comparing intervention delivery with and without this component.…”
Section: Discussionmentioning
confidence: 99%
“….Narrative health communication is a form of persuasive communication in which a health message is presented in the form of a fictional or nonfictional story, as opposed to being presented as statistical evidence or arguments to promote healthrelated behaviours 18. …”
mentioning
confidence: 99%